1981
DOI: 10.1128/aac.19.3.424
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of 2',3'-dideoxyadenosine in vivo and in vitro

Abstract: 2',3'-Dideoxyadenosine (DDA) was shown not only to possess antibacterial activity in vitro against a variety of Enterobacteriaceae, but also to be effective in vivo, DDA was active in experimental mouse infections by the oral route against 5 Salmonella strains, 2 of 3 Arizona strains, 5 of 7 Citrobacter strains, 3 of 8 Klebsiella strains, 3 of 5 Escherichia strains, 1 of 3 Shigella strains, and 3 of 15 Serratia strains at concentrations generally well below the toxic level. Closely related compounds, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In addition, it has been reported that the microbiotas in body sites other than the gut, such as the oral microbiota, are also changed under ART 19 , 20 . Furthermore, in vitro studies have indicated that an NRTI, zidovudine (AZT), exhibits antibacterial effects 21 likely due to inhibition of bacterial polymerases and/or induction of the SOS DNA damage response 22 25 . This evidence indicates that the gut microbiota of HIV-1-infected patients may be linked to gastrointestinal defects even under short-term ART.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that the microbiotas in body sites other than the gut, such as the oral microbiota, are also changed under ART 19 , 20 . Furthermore, in vitro studies have indicated that an NRTI, zidovudine (AZT), exhibits antibacterial effects 21 likely due to inhibition of bacterial polymerases and/or induction of the SOS DNA damage response 22 25 . This evidence indicates that the gut microbiota of HIV-1-infected patients may be linked to gastrointestinal defects even under short-term ART.…”
Section: Introductionmentioning
confidence: 99%
“…Second, metabolic inactivation of nucleosides such as ddA and ddC may occur because of deamination (7,8,30,39). Third, there appear to be differences in the abilities of microbial and mammalian DNA polymerases to incorporate dideoxynucleoside triphosphates into growing DNA chains (1,6,18,38); there also may be differences in the proofreading functions of various DNA polymerases or VOL. 34,1990 on May 12, 2018 by guest http://aac.asm.org/ Downloaded from in other processes associated with the removal or repair of incorporated dideoxynucleotides (18).…”
Section: Resultsmentioning
confidence: 99%
“…ddl, ddG, ddC, ddT, and D4T were inactive at 1,000 pg/ml. act as DNA chain terminators (1,6,13,38,39), it would be expected that they induce the SOS response. However, AZT and the dideoxynucleosides are structurally related to classical antimetabolites (18,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…research aiming to repurpose existing nucleotide analog drugs that are commonly used in immunomediated conditions, neoplasia, or viral therapies identified multiple drug candidates with an in vitro antibacterial activity [16]. Early experiments on the antibacterial action of 2',3'-dideoxyadenosine (ddATP) were observed in vitro and in vivo for several bacteria [17,18]. Recent studies found the growth inhibition potential of purine analogs in multiple commensal and pathogenic gastrointestinal bacteria [19,20] caused by a disruption in the mechanisms of DNA replication or even inducing DNA break [21], but none of those studies included Corynebacterium species.…”
Section: Introductionmentioning
confidence: 99%